2015
DOI: 10.1155/2015/265751
|View full text |Cite
|
Sign up to set email alerts
|

The Alpaca Melanocortin 1 Receptor: Gene Mutations, Transcripts, and Relative Levels of Expression in Ventral Skin Biopsies

Abstract: The objectives of the present study were to characterize the MC1R gene, its transcripts and the single nucleotide polymorphisms (SNPs) associated with coat color in alpaca. Full length cDNA amplification revealed the presence of two transcripts, named as F1 and F2, differing only in the length of their 5′-terminal untranslated region (UTR) sequences and presenting a color specific expression. Whereas the F1 transcript was common to white and colored (black and brown) alpaca phenotypes, the shorter F2 transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
2
14
1
8
Order By: Relevance
“…In contrast to other domestic species, coat color genomics in camelids had a late start, even though fiber color is an important trait for the alpaca industry (Morante et al, 2009) and there is an interest for breeding white or black dromedaries in some Arabian countries (Almathen et al, 2018). A few studies in alpacas have associated mutations in ASIP with the black color (Feeley et al, 2011; Chandramohan et al, 2013) and identified MC1R mutations that may determine light phenotypes, though the findings about the alpaca MC1R remain inconclusive (Feeley and Munyard, 2009; Guridi et al, 2011; Chandramohan et al, 2015). Research on dromedary color genes is even more recent with just two publications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other domestic species, coat color genomics in camelids had a late start, even though fiber color is an important trait for the alpaca industry (Morante et al, 2009) and there is an interest for breeding white or black dromedaries in some Arabian countries (Almathen et al, 2018). A few studies in alpacas have associated mutations in ASIP with the black color (Feeley et al, 2011; Chandramohan et al, 2013) and identified MC1R mutations that may determine light phenotypes, though the findings about the alpaca MC1R remain inconclusive (Feeley and Munyard, 2009; Guridi et al, 2011; Chandramohan et al, 2015). Research on dromedary color genes is even more recent with just two publications.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms that control pigmentation in camelids have mainly been studied in alpacas ( Vicugna pacos ). Different authors have studied MC1R (Powell et al, 2008; Feeley and Munyard, 2009; Guridi et al, 2011; Chandramohan et al, 2015), ASIP (Feeley et al, 2011; Chandramohan et al, 2013), TYR , and MATP genes (Cransberg and Munyard, 2011) in relation to alpaca coat colors. However, in llamas the mechanisms that control pigmentation are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate polymorphisms at MC1R and ASIP genes which may impair the structure and functionality of both proteins have been already shown to affect coat colour in this species (Powell et al 2008;Feeley and Munyard 2009;Bathrachalam et al 2011;Feeley et al 2011;Guridi et al 2011;Chandramohan et al 2013Chandramohan et al , 2015. In fact, the Agouti locus in white and coloured (black and brown) alpacas has been found to be affected by three different mutations consisting in two independent SNPs and one deletion of 57 bp (Feeley et al 2011;Chandramohan et al 2013).…”
Section: Introductionmentioning
confidence: 99%